(untitled) (UNIZIK Journal of STM Education, 2023)
This study investigated the impact of video analysis on teaching practice performance among Colleges of education in North -West Zone Nigeria. The research design adopts for the study was pure experimental design specifically, Post-test only Control Group design. The population consists of 1,770 NCE II Chemistry Students from eight(8) Colleges of Education, a sample of 105 N.C.E II were drawn from the population using simple random sampling technique and were categorized into Experimental and Control groups. Teaching Practice Performance Assessment Sheet (TPASS) with a reliability coefficient of 0.79 determined using Pearson Product Moment Correlation (PPMC) was the instrument used for data collection. One research question and one research hypothesis were raised to guide the study and analysed using Mean and independent t- test. Findings from the study revealed that Pre-service Chemistry teachers exposed to Video- self, and peer - analysis performed better in their teaching practice exercise than their counterparts in the Control group who were not exposed to video self and peer analysis. Based on the findings of the study, it was concluded that video -self, and peer-analysis of assessment enabled pre-service chemistry teachers perform better in their teaching practice exercise. Based on the findings of the study it was recommended that video should be used as a tool for observation and feedback during teaching exercise in teacher education programmes.